How soap bubbles freeze - S. Farzad Ahmadi (Nature Portfolio, 2019)
While the physics of freezing water droplets are known, it is less known how bubbles freeze. The authors investigate the physics of freezing soap bubbles and identify two distinct freezing modes, depending on whether the surroundings are warmer or colder than the melting temperature.